Dynamically controlled hydrocarbon column heights in fault bounded traps of the Hammerfest Basin, SW Barents Sea. Fault valve theory applied to the Snøhvit field - Kiss, Akos (UiT Norges arktiske universitet, 2019)
During initial exploration efforts in the Barents Sea several gas prone and underfilled prospects were drilled which significantly dropped the interest in the area. The Hammerfest Basin however turned out to hold significant hydrocarbon volumes. Although still mostly underfilled, the discoveries here today make up the Snøhvit oil and gas field. The Hammerfest Basin is an overfilled petroleum basin, meaning that the several source intervals have produced enough hydrocarbons over time to fill all the traps. This, and the hydrocarbon shows below the hydrocarbon-water contacts inside the traps indicate that the reason behind underfilled structures is leakage. This means that the main exploration risk in the area is trap integrity. Given the large amount of evidence for fault-assisted remigration, this thesis focuses on explaining the hydrocarbon column heights observed today in these structures with the help of fault valve theory. The theory suggests that a subset of faults oriented at the right angles to the stress field can control the pore pressures in a pressure compartment in a dynamic equilibrium. When pressure increases with hydrocarbon charge, or gas dissolution the effective stress drops which can reactivate the faults leading to the leakage of hydrocarbons from the trap. In this study, the slip tendencies of faults around the Albatross, Snøhvit and Askeladd structures were calculated and plotted on the interpreted fault planes. This gave the critical pressure perturbations of the faults, i.e. the pressure increase needed to cause slip on them. Faults and fault segments with low critical pressure perturbations are regarded as areas of high risk of leakage. After identifying high risk segments, their intersection with the top reservoir was found and compared with the level of hydrocarbon-water contacts. On Albatross Sør and Snøhvit Nord high risk faults and fault intersections intersect the top reservoir on the level of the gas-water contact. On Albatross and Snøhvit, both of which have leaked considerably, ...